Intrinsic ATR signaling shapes DNA end resection and suppresses toxic DNA-PKcs signaling. (1st May 2020) - Dibitetto, Diego; Sims, Jennie R; Ascenção, Carolline F R; Feng, Kevin; Kim, Dongsung; Oberly, Susannah; Freire, Raimundo; Smolka, Marcus B
Abstract: Most cancer cells experience oncogene-induced replication stress and, as a result, exhibit high intrinsic activation of the ATR kinase. Although cancer cells often become more dependent on ATR for survival, the precise mechanism by which ATR signaling ensures cancer cell fitness and viability remains incompletely understood. Here, we find that intrinsic ATR signaling is crucial for the ability of cancer cells to promote DNA end resection, the first step in homology-directed DNA repair. Inhibition of ATR over multiple cell division cycles depletes the pool of pro-resection factors and prevents the engagement of RAD51 as well as RAD52 at nuclear foci, leading to toxic DNA-PKcs signaling and hypersensitivity to PARP inhibitors. The effect is markedly distinct from acute ATR inhibition, which blocks RAD51-mediated repair but not resection and engagement of RAD52. Our findings reveal a key pro-resection function for ATR and define how ATR inhibitors can be used for effective manipulation of DNA end resection capacity and DNA repair outcomes in cancer cells.